URBAN SLUM COMMUNITIES PERCEPTION OF DRINKING WATER SUPPLY IN BEKASI MUNICIPALITY - Chandra R. P. Situmorang, Djoko M. Hartono*, Setyo Sarwanto Mursidik and Linda Darmajanti (Chelonian Research Foundation, 2023)
This study aims to find out the urban slum communities' perception and problems regarding the fulfillment of the drinking water supply in Bekasi. Perception data is collected by conducting interviews and survey with the community in slum areas. Quantitative methods are used to evaluate social, economic, and environmental factors carried by questionnaires. From a total of 767 respondents, 65% (502 respondents) of them did not have access to piped drinking water. They meet the needs of clean water sources by buying gallons of water (52.2%), using groundwater (16%), and joint or shared piped drinking water (14%). Keywords: Bekasi; low-income people; perception; slum area; water drinking